2009
DOI: 10.1590/s1415-47572009000300011
|View full text |Cite
|
Sign up to set email alerts
|

The association of CAPN1 316 marker genotypes with growth and meat quality traits of steers finished on pasture

Abstract: The objective of this paper was to determine the association of a SNP in the μ-calpain gene at position 316 with growth and quality of meat traits of steers grown on pasture. Fifty-nine Brangus and 20 Angus steers were genotyped for CAPN1 316. Warner Bratzler shear force was measured in l. lumborum samples after a 7-day aging period. A multivariate analysis of variance was performed, including shear force (WBSF), final weight (FW), average daily gain (ADG), backfat thickness (BFT), average monthly fat thicknes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 5 publications
2
20
0
4
Order By: Relevance
“…Animals with the GG genotype had +52.7 kg heavier LW and +34.4 kg heavier HCW compared to the CC genotype in the present study. In the literature, CAPN1 G316A was evaluated as an effective marker on beef tenderness in several studies indicating that the C allele is associated with more tender meat (Casas et al, 2005;Corva et al, 2007;Gill et al, 2009;Miquel et al, 2009;Smith et al, 2009;Curi et al, 2010). It has been shown that, along with loci affecting beef tenderness, other loci associated with weaning weight and carcass weights were mapped to bovine chromosome 29 (Casas et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Animals with the GG genotype had +52.7 kg heavier LW and +34.4 kg heavier HCW compared to the CC genotype in the present study. In the literature, CAPN1 G316A was evaluated as an effective marker on beef tenderness in several studies indicating that the C allele is associated with more tender meat (Casas et al, 2005;Corva et al, 2007;Gill et al, 2009;Miquel et al, 2009;Smith et al, 2009;Curi et al, 2010). It has been shown that, along with loci affecting beef tenderness, other loci associated with weaning weight and carcass weights were mapped to bovine chromosome 29 (Casas et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that, along with loci affecting beef tenderness, other loci associated with weaning weight and carcass weights were mapped to bovine chromosome 29 (Casas et al, 2005). Miquel et al (2009) reported that final weight and average daily gain differentiated between the CAPN1 G316A marker genotypes and that choosing animals with the favourable marker genotype (CC) for tenderness resulted in a selection of animals with lower average daily gain and final weight in Angus and Brangus steers. In addition, Pintos and Corva (2011) found significant associations between the same marker with birth weight, weaning weight and live weight recorded at 18 months of age in Angus cattle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…El polimorfismo CAPN1-316 está relacionado con variaciones en las características de ganancia en peso vivo y peso a la matanza en animales de las razas Angus y Brangus criados bajo pastoreo y sacrificados a un espesor de grasa dorsal promedio de 6.0 mm (Miquel et al, 2009). 91 %, 0 %, 9 %, respectivamente.…”
Section: Frecuencia De Capn-316unclassified